Effects of chocolate milk consumption on markers of muscle recovery following soccer training: a randomized cross-over study - Womack Christopher J; Moore Rebecca W; Moran Charles W; Saunders Michael J; Gilson Stephanie F; Todd M Kent (Taylor & Francis Group, 2010)
Abstract Background The efficacy of chocolate milk (CM) as a recovery beverage following a period of increased training duration (ITD) was studied in intercollegiate soccer players. Methods 13 subjects completed one week of normal 'baseline' training followed by four days of ITD. After each day of ITD, subjects received either a high-carbohydrate (504 kcal; CHO: 122 g; 2 g Fat) or isocaloric CM (504 kcal; 84 g CHO; 28 g Pro; 7 g Fat) recovery beverage. Serum creatine kinase (CK), myoglobin (Mb), muscle soreness, fatigue ratings and isometric quadriceps force (MVC) were obtained prior to ITD, and following 2- and 4-days of ITD. Performance tests (T-drill, vertical jump) were performed within training sessions. Treatments were administered in a randomly counterbalanced protocol, and subjects repeated the procedures with the alternate beverage following a two-week washout period. Results Mean daily training time and HR increased (p < 0.05) between baseline training and ITD, with no differences between treatments. No treatment*time effects were observed for Mb, muscle soreness, fatigue ratings and MVC. However, serum CK was significantly lower (p < 0.05) following four days of ITD with CM (316.9 ± 188.3 U·L-1) compared to CHO (431.6 ± 310.8 U·L-1). No treatment differences were observed for the performance tests. Conclusions Post-exercise CM provided similar muscle recovery responses to an isocaloric CHO beverage during four-days of ITD. Future studies should investigate if the attenuated CK levels observed with CM have functional significance during more demanding periods of training.